2023
DOI: 10.3390/ijms24021337
|View full text |Cite
|
Sign up to set email alerts
|

The Machinery of Exosomes: Biogenesis, Release, and Uptake

Abstract: Exosomes are a subtype of membrane-contained vesicles 40–200 nm in diameter that are secreted by cells into their surroundings. By transporting proteins, lipids, mRNA, miRNA, lncRNA, and DNA, exosomes are able to perform such vital functions as maintaining cellular homeostasis, removing cellular debris, and facilitating intercellular and interorgan communication. Exosomes travel in all body fluids and deliver their molecular messages in autocrine, paracrine as well as endocrine manners. In recent years, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(92 citation statements)
references
References 118 publications
0
91
0
1
Order By: Relevance
“…One of them can be associated with an RNA-induced silencing complex, and the other is found in exosomes, microvesicles, and apoptotic bodies [ 42 ]. Exosomes contain different proteins, microRNAs, mRNAs, and DNA [ 42 , 43 ]. It was shown that exosomal NUCB1 is involved in the pathophysiology of cancer and participates in EMT and atypical migration in non-tumor cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of them can be associated with an RNA-induced silencing complex, and the other is found in exosomes, microvesicles, and apoptotic bodies [ 42 ]. Exosomes contain different proteins, microRNAs, mRNAs, and DNA [ 42 , 43 ]. It was shown that exosomal NUCB1 is involved in the pathophysiology of cancer and participates in EMT and atypical migration in non-tumor cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…4.4 CD63 and VPS36 showed spatial-dependent colocalization and correlation after miRNA delivery Next, we verified the involvement of miR-125b-5p in the modulation of EV trafficking, focusing on the localization of EV-related proteins in pTr cells. VPS36 (miR-125b-5p target and marker of ESCRT-II complex present in endosomes/MVBs [47]) and CD63 (marker of EVs [48]) were selected based on our recent studies pointing to embryonic signals as triggers of EV trafficking in endometrial luminal epithelial cells [26]. Regions of interest (ROIs) were set based on the overlapping localization of both proteins present in the highly visible and well-shaped cell borders (white) in comparison to the whole cell (Fig.…”
Section: Mir-125b-5p Is Efficiently Delivered To Ptr Cells and Intern...mentioning
confidence: 99%
“…Exosomes are the smallest extracellular vesicles (EVs) which also include two other larger subtypes (microvesicles and apoptotic bodies) . EVs contain a distinctive signature of macromolecules derived from parental cells, such as lipids, nucleic acids, proteins, and metabolites, and many of them are present both in the lumen and on the membrane of an EV. Initially, EVs were regarded as remnants of cellular decay or indicative of waste elimination processes associated with cell death. ,, However, subsequent research has indicated that these vesicles are actively secreted by donor cells into the extracellular milieu, undertaking diverse biological roles, such as intercellular communication and exchange of proteins and genetic materials between an originating cell and its neighboring cells. , These EVs are taken up into recipient cells through one of three processes: (1) endocytosis, (2) interaction between exosomal surface proteins and plasma membrane receptors, or (3) fusion with the recipient cell’s membrane . Interestingly, recent research suggests that MSC-secreted exosomes can substitute stem cell-based treatments in numerous wound-healing animal models. , Because of their distinctive properties, for instance, low immunogenicity, intrinsic stability, and excellent cell and tissue penetration capacity, exosomes have been explored as delivery vehicles to transport therapeutic agents including small molecules, nucleic acids, and proteins to cells .…”
Section: Introductionmentioning
confidence: 99%